1998
DOI: 10.1021/jm9803525
|View full text |Cite
|
Sign up to set email alerts
|

A Novel (Benzodifuranyl)aminoalkane with Extremely Potent Activity at the 5-HT2A Receptor

Abstract: A major focus of our research for a number of years has been to understand the structure-activity relationship (SAR) of classical hallucinogens and their derivatives, the pharmacological action of which is believed to be mediated primarily by agonist activity at the serotonin 5-HT 2A receptor. 2,3 In particular we have sought to understand the relationship between the modes of binding of the hallucinogens containing an indole nucleus, including LSD and psilocybin, and those containing a benzene nucleus, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 12 publications
2
78
0
3
Order By: Relevance
“…9 In a prior study, we also had shown that expansion of both furan rings to the larger, six-membered pyrans led to a nearly ten-fold loss of affinity and in vivo behavioral activity, although compounds 3 were still significantly more potent than the flexible prototype 1. 7 In this report, new compounds 4-6 further support those earlier observations and confirm the proper orientation of the arene oxygen lone pair electrons for optimal activity at the 5-HT 2A receptor.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…9 In a prior study, we also had shown that expansion of both furan rings to the larger, six-membered pyrans led to a nearly ten-fold loss of affinity and in vivo behavioral activity, although compounds 3 were still significantly more potent than the flexible prototype 1. 7 In this report, new compounds 4-6 further support those earlier observations and confirm the proper orientation of the arene oxygen lone pair electrons for optimal activity at the 5-HT 2A receptor.…”
Section: Discussionmentioning
confidence: 90%
“…Aromatization of the furan ring of 4b was accomplished using a method analogous to that employed by Parker, et al 9 As shown in Scheme 3, dihydrofuran 17b was protected as its Ntrifluoroacetamide 19, brominated to provide 20, and then oxidized using 2,3-dichloro-5,6-dicyano-l,4-benzoquinone (DDQ) to afford the protected intermediate 21. Deprotection in strong base gave 6, the final target molecule.…”
Section: Chemistrymentioning
confidence: 99%
“…To validate the established model, two separately synthesized potential hallucinogenic compounds [20] ( Figure 6) were used for prediction. The predicted values suggest that compound 2 have higher activity than compound 1.…”
Section: Comfa Resultsmentioning
confidence: 99%
“…The chemical structure of Bromo-dragonFLY is shown in comparison with serotonin in Figure 1. These compounds have been developed as potent research tools for investigation of the serotonin receptor family, in particular the 5-HT2 subfamily of receptors [7][8][9][10]. These agents were thought to have a potential role in the development of novel antidepressant drugs that stimulate release of serotonin, differing from conventional antidepressants that inhibit the reuptake of serotonin.…”
Section: Discussionmentioning
confidence: 99%